Analisis Komprehensif Teori Evaluasi Pendidikan dalam Pembelajaran - Ja'far Siddik; Usman Usman; Nor Fadhilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Educational evaluation is an essential part of the learning process, serving to measure the achievement of educational goals and to continuously improve the quality of learning. This study aims to analyze educational evaluation theory in learning, including the basic concepts of evaluation, evaluation models and approaches, and their relevance to 21st-century learning. The study employed a qualitative approach with the Systematic Literature Review (SLR) method through a review of various reputable international journals published between 2020 and 2025. Research data was obtained from various scientific sources such as Scopus, ScienceDirect, Springer, Taylor & Francis, and Sage Journals. The results show that educational evaluation theory is evolving from outcome-oriented evaluation to a more holistic, authentic, and competency-based evaluation. Evaluation models such as Goal-Oriented Evaluation, formative and summative evaluation, the CIPP model, authentic assessment, and diagnostic assessment play an important role in supporting modern learning. In addition, the integration of digital technology in learning evaluation provides opportunities to create a more adaptive and contextual assessment system.